The Social and Religious Morals of Children in Fransisca Emilia and Vincentia's Di Mana Adik? Storybook - Marwany; Prawening, Cesilia; Suta Wardianto, Bayu; Woelan Fadini Zul Qaedah, Noer (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Moral value as an ethnic thing for human life, this is because there is a moral value that must be possessed by every individual as a standard for a person to behave and behave in society. The cultivation of moral values must be instilled from an early age. One easy way to bring moral values to children is through stories or fairy tales. Fairy tales as part of children's literature that are entertaining and educating their readers. From here, it is important to conduct research on the moral aspects contained in the Di Mana Adik? storybook by Fransisca emilia and Vincentia. The method used is qualitative descriptive. The object of this study is the stories contained in Di Mana Adik? stories?. The research uses qualitative descriptive research methods. The data in the study were analyzed using content analysis techniques in the form of text, data collection using library techniques, listening techniques, and note-taking techniques. The results of the research obtained from the analysis are the existence of moral values, namely social values and religious values. The values contained in the two moral values are hard work, affection, responsibility, and independence. These values are an important part of a moral that must be possessed by children from an early age